IMPROVING PHYSICO-CHEMICAL CHARACTERISTIC AND PALATABILITY OF KING GRASS (Pennisetum hybrid) SILAGE BY INOCULATION OF Lactobacillus plantarum - Saccharomyces cerevisiae CONSORTIA AND ADDITION OF RICE BRAN - Yantyati Widyastuti; Ristianto Utomo; Lies Mira Yusiati; Ahmad Sofyan (Buletin Peternakan, 2017)
This study was conducted to determine effectiveness of inoculants consisted of lactic acid bacteria Lactobacillus plantarum (Lp) and yeast Saccharomyces cerevisiae (Sc) combined with addition of rice bran on the physico-chemical characteristics and palatability of king grass (Pennisetum hybrid) silage. The experiment was arranged on the factorial randomized design (3x3) consisting of the inoculants treatments (control, Lp, Lp+Sc) and the addition level of rice bran (0, 5 and 10%). The measured variables were physico-chemical characteristics i.e. colour, odour, pH, lactic acid, Fleigh points, and palatability of silage. Inoculation of Lp and Lp+Sc improved silage odour and reduced fungal contamination. Silage was treated by Lp+Sc and rice bran (5-10%) showed reduction of pH and an increase of lactic acid and Fleigh points. However, interaction between inoculants and rice bran treatment was not significance. Either inoculation or addition of rice bran tended to enhance the palatability of silage in cattle. It concluded that the addition of inoculants L. plantarum and S. cerevisiae with/without addition of 5-10% rice bran could improve the physico-chemical characteristics of silage and its palatability to ruminant.